2022
DOI: 10.1007/s11263-022-01605-9
|View full text |Cite
|
Sign up to set email alerts
|

Facial Kinship Verification: A Comprehensive Review and Outlook

Abstract: The goal of Facial Kinship Verification (FKV) is to automatically determine whether two individuals have a kin relationship or not from their given facial images or videos. It is an emerging and challenging problem that has attracted increasing attention due to its practical applications. Over the past decade, significant progress has been achieved in this new field. Handcrafted features and deep learning techniques have been widely studied in FKV. The goal of this paper is to conduct a comprehensive review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 163 publications
(170 reference statements)
0
14
0
Order By: Relevance
“…Then the metric learning-based methods [3], [37] were proposed to separate the kin and non-kin pairs. With the development of deep learning, many methods with different motivations were raised [1]. Among those, Li et al [38] proposed a Siamese network with the similarity metric to learn the discriminative features for kinship verification.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Then the metric learning-based methods [3], [37] were proposed to separate the kin and non-kin pairs. With the development of deep learning, many methods with different motivations were raised [1]. Among those, Li et al [38] proposed a Siamese network with the similarity metric to learn the discriminative features for kinship verification.…”
Section: Related Workmentioning
confidence: 99%
“…On the basis of image-based studies, to capture multi-source information, researchers proposed to study the kinship verification from facial videos. Compared with image-based studies [21], the works on facial videos [32]- [34] can only be found with a limited scale [1]. At the beginning, the constrained facial video dataset was used.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…F ACIAL kinship verification (FKV) aims at automatically determining whether two individuals have a kin relationship or not from their given facial images or videos [1]. Since the seminar work by Fang et.…”
Section: Introductionmentioning
confidence: 99%